Supply chain strategies and disaster planning - Venkataraman, Ray R. (SAGE Knowledge. Cases., 2017)
This case illustrates how firms should formulate and implement global operations and supply chain strategies for risk management to alleviate disruptions to their operations and supply chains from natural disasters or safety and security problems. The fact that only 10% of businesses have contingency plans in place to cope with operations and supply chain disruptions despite the likelihood of disasters means disaster planning/risk management should be an essential part of their supply chain strategy.